Penemuan Hukum dalam Sistem Peradilan Indonesia: Suatu Kajian Teoretis dan Normatif Berbasis Studi Kepustakaan - Slamet Riyadi; Nur Ahmad Fadillah; Ade Hasan Santoso; Asep Sapsudin (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
Legal discovery (rechtsvinding) by judges has increasingly become a central phenomenon in the Indonesian judicial system, particularly in response to normative gaps, ambiguous regulations, and conflicts of legal norms. This study aims to analyze the characteristics, techniques, and implications of legal discovery in the Indonesian judiciary from a theoretical and normative perspective. The research employs a normative legal research method with a library research approach, examining Indonesian legal literature, doctrines, and court decisions published between 2021 and 2025. The findings indicate that legal discovery is consistently practiced by judges as a mechanism to bridge written law and social reality. Judges apply various interpretative techniques, including grammatical, systematic, teleological interpretation, legal analogy, and value-based approaches, depending on the nature of the case. Legal discovery is generally oriented toward achieving substantive justice while maintaining legal certainty and judicial legitimacy. However, differences in interpretative techniques may potentially affect the consistency of judicial decisions. This study concludes that legal discovery is a legitimate and necessary judicial practice, provided it is carried out within clear normative and methodological boundaries. The implications of this research highlight the importance of strengthening interpretative guidelines and judicial reasoning capacity to ensure accountable and consistent legal discovery in Indonesian courts. Keywords: legal discovery; judicial interpretation; rechtsvinding; Indonesian judiciary; normative legal research